Industrial location economics - McCann, Philip, 1964- (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
Because space is not homogenous, economic activities occur in different locations. Understanding the reasons behind this and understanding exactly how industries are spatially organized is the central theme of this title. It discusses different aspects of industrial location behaviour from a variety of theoretical and empirical perspectives. Each of the analytical traditions provides insights into the nature of industrial location behaviour and the factors which can influence it.
Includes bibliographical references and index.
oif 29/01/14
Loan
Keywords: International business enterprises -- Location; Industrial sites; Business relocation; Industrial location; Space in economics